Comprehensive molecular and clinicopathological profiling of desmoid tumours. (March 2021) - Kohsaka, Shinji; Hirata, Makoto; Ikegami, Masachika; Ueno, Toshihide; Kojima, Shinya; Sakai, Tomohisa; Ito, Kan; Naka, Norifumi; Ogura, Koichi; Kawai, Akira; Iwata, Shintaro; Okuma, Tomotake; et al.
Abstract: Previous studies have not clearly identified a prognostic factor for desmoid tumours (DT). Whole-exome sequencing (WES) and/or RNA sequencing (RNA-seq) were performed in 64 cases of DT to investigate the molecular profiles in combination with the clinicopathological characteristics. CTNNB1 mutations with specific hotspots were identified in 56 cases (87.5%). A copy number loss in chromosome 6 (chr6) was identified in 14 cases (21.9%). Clustering based on the mRNA expression profiles was predictive of the patients' prognoses. The risk score generated by the expression of a three-gene set ( IFI6, LGMN, and CKLF ) was a strong prognostic marker for recurrence-free survival (RFS) in our cohort. In risk groups stratified by the expression of IFI6, the hazard ratio for recurrence-free survival in the high-risk group relative to the low-risk group was 12.12 (95% confidence interval: 1.56–94.2; p = 8.0 × 10 6 ). In conclusion, CTNNB1 mutations and a chr6 copy number loss are likely the causative mutations underlying the tumorigenesis of DT while the gene expression profiles may help to differentiate patients who would be good candidates for wait-and-see management and those who might benefit from additional systemic or radiation therapies. Highlights: CTNNB1 mutations and loss in chr6 are the causative mutations of desmoid tumours. The expression of IFI6 is the most significant marker to stratify the prognosis. High-risk patients are potentially good candidates for wait-and-see management.